Clinical outcomes of COVID-19 in hemodialysis patients - Adwan, Lina; Al-Sadi, Tala; Shawakha, Shorouq; Al-Shami, Ni’meh A. (Frontiers in Medicine, 2023)
Background The coronavirus disease 2019 (COVID-19) is known for its effects on the respiratory system. Three years after the pandemic morbid and mortal consequences, growing evidence is showing that the disease also has adverse outcomes and complications on additional organs including the kidneys. This study aims at investigating the effects of COVID-19 on hemodialysis patients receiving services at Palestine Medical Complex (PMC) kidney dialysis department, and to identify mortality related risk factors. Methods In April 2022, data was collected using the electronic medical records system for the dialysis department at PMC. The study included all PMC hemodialysis patients that were infected with COVID-19 between January 2020–April 2022. The collected data included patient demographics, clinical features, laboratory tests, dialysis frequency and the disease outcome. Results The results showed that the patients’ outcomes and dialysis frequency were impacted by their blood urea nitrogen (BUN), serum creatinine (SCr) and calcium levels. About one third of the study population died after being infected with COVID-19. The frequency of dialysis was also affected by the presence of comorbidities like hypertension, diabetes mellitus (DM) and myocardial infarction (MI). Conclusion This study found that there was a high mortality rate within the hemodialysis patients infected with COVID-19. Having comorbidities affected the frequency of dialysis following COVID-19 infection. Dialysis patients should be protected from infections such as COVID-19 and their comorbidities should be monitored and kept under control as much as possible.